2014
DOI: 10.1038/ncomms6590
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism-based inactivator of glycoside hydrolases involving formation of a transient non-classical carbocation

Abstract: The design of mechanism-based enzyme inactivators to generate chemical probes for biological research is an important challenge in carbohydrate chemistry. Here we describe the synthesis and biological evaluation of a novel carbocyclic mechanism-based inactivator of galactosidases (glycoside hydrolase families 27 and 36). Upon catalysis of this unnatural substrate, a transient non-classical carbocation forms within the enzyme active site. We show that the inactivation event, which proceeds via a bicyclobutonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Also, hydrolysis of the Asp327‐linked carbasugar intermediate, which has only been detected previously by mass spectrometry,4 proceeds via a perturbed TS free energy pathway in the solid state. These two observations inspired us to design a second‐generation inactivator with a significantly lower reactivation rate, which would enable structural analysis of the covalently bound complex with Tm GalA in the solid state.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Also, hydrolysis of the Asp327‐linked carbasugar intermediate, which has only been detected previously by mass spectrometry,4 proceeds via a perturbed TS free energy pathway in the solid state. These two observations inspired us to design a second‐generation inactivator with a significantly lower reactivation rate, which would enable structural analysis of the covalently bound complex with Tm GalA in the solid state.…”
mentioning
confidence: 73%
“…In both cases, pyranosylium ion like transition states (TSs), which can have half‐chair ( 4 H 3 / 3 H 4 ), boat ( 2,5 B/B 2,5 ), or envelope ( 4 E and 3 E) conformations (Figure 1 b),2, 3 are implicated. By exploiting this knowledge, we recently reported that the cyclopropyl‐containing carbasugar 1 is a mechanism‐based inactivator of an α‐ d ‐galactosidase from Thermotoga maritima ( Tm GalA; Figure 1 c) 4. Within the enzymatic active site, 1 likely forms a transient bicyclobutenium ion ( 1 + ), and enzyme inactivation occurs through alkylation of the catalytic nucleophile Asp 327.…”
mentioning
confidence: 99%
See 3 more Smart Citations